Identity confidence estimation of manoeuvring aircraft - Holtzhausen, Petrus Jacobus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.